Assessing energy business cases implemented in the North Sea Region and strategy recommendations. (15th June 2016) - Xu, Bing; Nayak, Amar; Gray, David; Ouenniche, Jamal
Highlights: Propose an integrated MCDA-based framework to benchmark DSM energy business cases. Address interests from various stakeholders, different forms of data, both fuzzy and crisp relations. Contract optimisation and offering reserve capacity strategies works well. Lack of strong incentives for firms to implement energy solutions on a larger scale. Need to design attractive incentive programmes to attract more industry engagement. Abstract: e-harbours is a unique European project that was set out to identify viable energy business cases on the exploitation of energy flexibility, which optimise their operations to match energy demand and supply while taking account of the additional volatility in supply caused by renewable energy sources, improve energy efficiency, and reduce dependence on fossil fuels. In this paper, we propose an integrated multi-criteria decision analysis based framework to assess the relative performance of 21 energy business cases, which implemented different demand-side management strategies. Our proposed methodology has the ability to address complex problems involving multiple conflicting interests from various stakeholders, different forms of data, and different fuzzy and crisp relations. We find that business cases based on contract optimisation and offering reserve capacity were ranked relatively high, while those based on trading on the wholesale market or hybrid approaches fared less well. Despite finding viable pilot business cases, e-harbours found that there was little enthusiasm among industrial partners to scale up the pilots. Consequently, EU governments should consider offering attractive incentive programmes for industry engagement in achieving their objectives in reducing greenhouse gas emissions, improving energy supply security, diversifying energy supplies, and improving Europe's industrial competitiveness.